A highly conserved basidiomycete peptide synthetase produces a trimeric hydroxamate siderophore - Brandenburger, Eileen; Gressler, Markus; Leonhardt, Robin; Lackner, Gerald; Habel, Andreas; Hertweck, Christian; Brock, Matthias; Hoffmeister, Dirk (American Society for Microbiology, 2017)
The model white-rot basidiomycete Ceriporiopsis (Gelatoporia) subvermispora B encodes putative natural product biosynthesis genes. Among them is the gene for the seven-domain nonribosomal peptide synthetase CsNPS2. It is a member of the as-yet uncharacterized fungal type VI siderophore synthetase family which is highly conserved and widely distributed among the basidiomycetes. These enzymes include only one adenylation (A) domain, i.e., one complete peptide synthetase module and two thiolation/condensation (T-C) di-domain partial modules which, together, constitute an AT1C1T2C2T3C3 domain setup. The full-length CsNPS2 enzyme (274.5 kDa) was heterologously produced as polyhistidine fusion in Aspergillus niger as soluble and active protein. N5-acetyl-N5-hydroxy-L-ornithine (L-AHO) and N5-cis anhydromevalonyl-N5-hydroxy-L-ornithine (L-AMHO) were accepted as substrates, as assessed in vitro using the substrate-dependent [32P] ATP-pyrophosphate radioisotope exchange assay. Full-length holo-CsNPS2 catalyzed amide bond formation between three L-AHO molecules to release the linear L-AHO trimer, called basidioferrin, as product in vitro, which was verified by LC-HRESIMS. Phylogenetic analyses suggest that type VI family siderophore synthetases are widespread in mushrooms and have evolved in a common ancestor of basidiomycetes.